Environvental impact of the activity si Ukraine: Detail history (1970-1980) - Besov, L. M. (History of science and technology, 2014)
It is shown as a rigid focus on manufacturing priorities brought amazing changes in the environment, ecological crisis deepened in society. Dominant technocratic paradigm of scientific, technical and production activities in social superseded svidomosti that the surrounding world exists not only to meet the needs of material.